Resection and reconstruction of the tracheal carina: Experimental evaluation - Carrera, Carlos; Gastambide, Carmelo; Delgado, Fernando; Rubí, Francisco; Crestanello, Francisco (Cirugía del Uruguay, 1975)
The present work discusses the procedures of direct reconstruction of the airway by Barclay's and Mathey's techniques, after carinal resections, in a series of 20 dogs. It remarks the technical aspects related to ventilation through the surgical field and the maintenance of tracheo-bronchial toilet during reconstruction. It concludes that Mathey's procedure is adequate to reconstruct the- carina after non extensive resections, while, Barclay's permits reconstructions after wider resections.